# Simplify. a/6b^3 + 5/9b^2 divided by 7/6b - 1/9b^3 Leave answers in factored and reduced form. Include parenthesis around polynomials in numerator and/or denominator.

### 1 Answer | Add Yours

The expression `(a/(6b^3) + 5/(9b^2))/(7/(6b) - 1/(9b^3))` has to be simplified.

`(a/(6b^3) + 5/(9b^2))/(7/(6b) - 1/(9b^3))`

= `((a9 + b*30)/(54*b^3))/((63b^2 - 6)/(54b^3))`

= `(a9 + b*30)/(63b^2 - 6)`

= `(3a + 10b)/(21b^2 - 2)`

**The expression `(a/(6b^3) + 5/(9b^2))/(7/(6b) - 1/(9b^3))` = `(3a + 10b)/(21b^2 - 2)` **